Sumber Daya Manusia, Teknologi Informasi, Sistem Akuntansi Manajemen dan Kinerja Manajerial UMKM dengan Ketidakpastian Lingkungan sebagai Variabel Moderasi - Abidin, Zainal; Furkan, Lalu M.; Suryani, Embun (E-Jurnal Akuntansi, 2021)
This study aims to analyze the effect of human resources, information technology, management accounting systems on managerial performance with environmental uncertainty as moderating. The research population was all 116 Pharmacy managers/owners in Mataram City. In this study, only two hypotheses were accepted, namely the second and third hypotheses, besides that the hypothesis was rejected. The results showed that human resources had a negative and insignificant effect on managerial performance at the Mataram City Pharmacy, while Information Technology and Management Accounting Systems had a positive and significant effect on managerial performance. Meanwhile, environmental uncertainty does not strengthen or weaken the influence of human resources, information technology and management accounting systems on managerial performance. Keywords : Human Resources; Information Technology; Management Accounting System; Environmental Uncertainty; Managerial Performance.